Moderation of Islamic Work Ethic Variables on the Influence of Work Environment, Work Motivation, Work Culture and Compensation on Employee Performance - Ridlo, Musalim; Rozaq, M Ahsin; Saputra, Yudi; Mochlasin, Mochlasin (Management Analysis Journal, 2022)
This study aims to analyze the effect of the work environment, work motivation, organizational culture, and compensation moderated by Islamic work ethic on employee performance. Methods of data collection by distributing questionnaires to the RSI Magelang City. The questionnaire was obtained and then tested as many as 80 respondents with the purposive sampling method. The data was then tested using multiple regression analysis and moderated analysis Regression (MRA) to determine the effect of the independent variable and the effect of moderation on the dependent variable with the help of the SPSS version 23 application. The results showed that (1) the work environment had a significant effect on employee performance. , (2) work motivation has no significant effect on employee performance, (3) organizational culture has no significant effect on employee performance, (4) compensation has a significant effect on employee performance, (5) Islamic work ethic is not able to moderate the independent variables, for example, the work environment, work motivation, and organizational culture for their influence on employee performance, but for the compensation variable it can be moderated by Islamic work ethic for its influence on employee performance with a negative coefficient.